CONTENT AND LANGUAGE ANALYSIS “THINK GLOBALLY ACT LOCALLY” FOR JUNIOR HIGH SCHOOL PUBLISHED BY MINISTRY OF EDUCATION AND CULTURE OF INDONESIA - Danul Aristiawan; Herman (Yavana Bhasha : Journal of English Language Education, 2021)
Textbook is one of the learning materials that can be used by teacher and students in order tohelp the teaching and learning process in the classroom. An analysis to a textbook is needed, moreoverafter the curriculum was launched. The object of the study is students English textbook entitled“ Think globally act locally” published by Ministry of Education and Culture of the Republic ofIndonesia. This study was designed in descriptive qualitative research because the object of the studywas a document book. Moreover, as the data was in the form of words and documents, so the datawere analyzed qualitatively. The results of the study show that the suitability of the material in thetextbook is 78.12%, which can be concluded that the material from the textbook has met the standardof content eligibility in the textbook. Meanwhile, the feasibility of using the language in the textbook is75%, which can be concluded that the book uses language in accordance with BSNP assessmentstandards